2019
DOI: 10.1021/acs.inorgchem.9b00437
|View full text |Cite
|
Sign up to set email alerts
|

The Puzzling Monopentamethylcyclopentadienyltitanium(III) Dichloride Reagent: Structure and Properties

Abstract: Following the track of the useful titanocene [Ti( 5 -C5H5)2Cl] reagent in organic synthesis, the related half-sandwich titanium(III) derivatives [Ti( 5 -C5R5)Cl2] are receiving increasing attention in radical chemistry of many catalyzed transformations. However, the structure of the active titanium(III) species remains unknown in the literature. Herein, we describe the synthesis, crystal structure, and electronic structure of titanium( III) aggregates of composition [{Ti( 5 -C5Me5)Cl2}n]. The thermolysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 80 publications
3
29
0
Order By: Relevance
“…The κ 2 ‐coordinated BH 4 groups agree with the long Ti⋅⋅⋅B distances of 2.389(4) and 2.402(3) Å when compared with that found (2.220(9) Å) for the κ 3 ‐BH 4 ligands of complex 4 [32] . The Ti−O bond length of 2.111(2) Å compares well with those found in other titanium(III) tetrahydrofuran adducts such as [Ti(η 5 ‐C 5 Me 5 )Cl 2 (thf)] (Ti−O=2.083(2) Å) [11,37] …”
Section: Resultssupporting
confidence: 81%
“…The κ 2 ‐coordinated BH 4 groups agree with the long Ti⋅⋅⋅B distances of 2.389(4) and 2.402(3) Å when compared with that found (2.220(9) Å) for the κ 3 ‐BH 4 ligands of complex 4 [32] . The Ti−O bond length of 2.111(2) Å compares well with those found in other titanium(III) tetrahydrofuran adducts such as [Ti(η 5 ‐C 5 Me 5 )Cl 2 (thf)] (Ti−O=2.083(2) Å) [11,37] …”
Section: Resultssupporting
confidence: 81%
“…Computational studies for the chloride-bridged dimer 4 showed a singlet ground state and a relatively large singlet–triplet energy gap . In accord with this strong antiferromagnetic interaction, diamagnetism is expected in the NMR spectra of complex 4 in a fashion similar to those suggested by NMR and electron paramagnetic resonance (EPR) spectroscopies in solution for the analogous dimeric complexes [{Ti­(η 5 -C 5 Me 4 Ph)­Cl­(μ-Cl)} 2 ] and [{Ti­(η 5 -C 5 (CH 2 Ph) 5 )­Cl­(μ-Cl)} 2 ], which show slightly longer Ti–Ti distances (3.335(1) and 3.374(2) Å, respectively) .…”
Section: Resultsmentioning
confidence: 66%
“…Compounds 4 – 6 were isolated after workup in 40–66% yields as highly air-sensitive green solids, which exhibit a good solubility in aromatic hydrocarbon solvents but are poorly soluble in hexane. We recently described the synthesis of crystals of the chloride complex 4 in higher yield (90%) by thermolysis of [Ti­(η 5 -C 5 Me 5 )­Cl 2 Me] in hexane . Crystals of compounds 5 and 6 were isolated after recrystallization in hot toluene, and those samples were used for X-ray crystal structure determinations and magnetic measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations were carried out with the Gaussian 16 package, using PBE0 as the density functional . This functional was already used with similar systems. , All atoms were represented with a def2-tzvp basis set with added D3 Grimme empirical dispersion . Geometry optimizations were performed without symmetry constraint, and vibrational analysis was used to confirm the presence of a local minimum .…”
Section: Computational Detailsmentioning
confidence: 99%